Piece of my heart - Clark, Mary Higgins; Burke, Alafair (Clark, Mary Higgins. Under suspicion novel., 2020)
A high-suspense follow-up to the best-selling "You Don't Own Me" finds the nuptials of television producer Laurie Moran and investigative host Alex Buckley nightmarishly upended by the sudden disappearance of Alex's seven-year-old nephew.